Efektifitas Pengembangan Lembar Kerja Peserta Didik Berbasis Keterampilan 4C Melalui Model Research Based Learning Untuk Pembelajaran Fisika - Zaka Putra Utama; Festiyed Festiyed (Jurnal Penelitian Pembelajaran Fisika, 2020)
Abstract. This study aims to describe the effectiveness of 4c skill-based LKPD on the Research Based Learning model for physics learning for high school students. The research method used is a research and development method by using the Plomp development model, namely Preliminary Research¸Prototype Phase and Assessment Phase . The instrument used was the LKPD effectiveness sheet seen from the 4c Skill of students. The results of the study indicate the value of an increase in analysis that LKPD through the Research Based Learning model is effective in efforts to improve the 4C skills of education participants. Keywords. LKPD, Research Based Learning, 4C SkillsKeywords. LKPD, Research Based Learning, 4C Skills